PELAKSANAAN KEGIATAN PADAT KARYA TUNAI DESA DI DESA TANJUNG SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2020 - Fika Sesita; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Congested Creation Cash village is activities originating from the Village Fund as form effort empowerment public in develop related potential with village and aim for welfare public village. Implementation activity at 20 H soil rice fields owned by managed farmer by BUMDes is starting on year 2017, when this Becomes source power public village Cape Simandolak. If experience failure in the planting process and results harvest so result in public will lost income because most public this only depend on Agriculture as his income.As for destination from study this is for knowing implement activity congested creation cash village in village Cape The sourced Simandolak from the Village Fund year 2020. Besides that also for knowing factor blocker inside Implementation activity congested creation cash village in village Cape Simandolak. Study this use method qualitative that describes the data in a descriptive. Next technique data collection used is interview and documentation. Whereas data source used is the primary data obtained from location study in the form of informant study and supported by secondary data that is documents related with method interviews, observations , and studies document . As for location study this that is Service Agriculture districts Kuantan Singingi and village Cape Simandolak.As for results and discussion from study this that is show that implementation activity Congested creation cash village in village Cape Simandolak 2020 is not yet done with maximum. Frequent problems occurs in the agricultural process like less PPL responsive when occur season drought , flood and attack pests. Implementation program activity Congested creation cash villages that use fund village in implementation as well as organization executor in accordance with ability each actors involved then group intended target for public farmer in the village Cape Simandolak that alone. As for factor blocker that is about budget , lack socialization knowledge and skills , still lack of connection communication with Service Agriculture about help. Final existence destination together in implementation activity congested creation cash village in Village Cape Simandolak so that the community future could independent.Keywords: Implementation, Solid Creation Cash Village (PKTD)